1991
DOI: 10.1002/etc.5620100903
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial mutagenicity and acute toxicity of solvent and aqueous extracts of soil samples from an abandoned chemical manufacturing site

Abstract: Using a grid pattern, a total of 50 soil borings (DCT 1 through DCT 50) were collected from an abandoned chemical manufacturing facility. Split samples were obtained from six cores collected from a centralized location near a former wastewater lagoon. An additional sample from the 2.1‐ to 2.4‐m depth of core DCT 20 was obtained as representative of the waste present on site. Three subsamples from each of the six cores or a total of 18 samples were sequentially extracted with methylene chloride and methanol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…However, this trend did not continue; the soil that contained the second greatest concentration of PAH (SoCal 3) was one of the least toxic samples. Previous studies completed on contaminated soils and sediments have also shown lack of consistent correlation between the results of chemical analyses and Microtox toxicity (True and Heyward 1990, Donnelly et al 1991, Jacobs et al 1993, as well as toxicity determined with fish and invertebrates (Athey et al 1989, Hoke et al 1990. Vigorous physical and chemical methods of contaminant extraction from soils tend to pull contaminants from particles that would not ordinarily occur in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this trend did not continue; the soil that contained the second greatest concentration of PAH (SoCal 3) was one of the least toxic samples. Previous studies completed on contaminated soils and sediments have also shown lack of consistent correlation between the results of chemical analyses and Microtox toxicity (True and Heyward 1990, Donnelly et al 1991, Jacobs et al 1993, as well as toxicity determined with fish and invertebrates (Athey et al 1989, Hoke et al 1990. Vigorous physical and chemical methods of contaminant extraction from soils tend to pull contaminants from particles that would not ordinarily occur in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…The test is short, only 72 h. The test has been applied in genotoxic studies on waste, contaminated soil, sewage sludge, and sediments Donelly et al, 1991;Kohl et al, 1989;Joutti and Ahtiainen, 1994). Speci"c Salmonella typhimurium strains with an obligatory requirement for histidine are used to test mutagenicity.…”
Section: Genotoxicitymentioning
confidence: 98%
“…in the light of genetic variation and the ability of organisms to adapt to stress factors, is still an open question (De Raat et al, 1990). The interpretation of test results is complicated by the fact that mutagenic activity is not only detected at contaminated sites but also in unpolluted soil (Kool et al, 1989;Brown et al, 1985) and often bears no clear relationship with the concentration of known mutagens (Donnelly et al, 1991).…”
Section: End-points Of the Assessmentmentioning
confidence: 98%